Memahami Doktrin Allah Tritunggal melalui Dialog Meditasi Hindu-Kristen (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to explore and deepen the understanding of the doctrine of the Holy Trinity through the approach of Hindu–Christian meditative dialogue. The doctrine of the Holy Trinity constitutes the central foundation of the Christian faith, understood as the unity and equality of the essence of the one God in three persons, namely the Father, the Son, and the Holy Spirit. However, explanations and interpretations of the Trinitarian doctrine are often regarded as complex and difficult to comprehend, not only by the general public but also by many Christians, particularly lay believers. Therefore, an alternative approach that is more communicative and contextual is needed so that this doctrine can be understood in a simpler and more reflective manner. One approach proposed in this study is the concept of Hindu–Christian meditative dialogue, which emphasizes the contemplative dimension and inner spiritual experience as means of theological understanding. This study employs a qualitative method using a literature-based approach, drawing on theological documents, books, scholarly journals, and other relevant literature as the primary data sources. The collected data and information are then systematically analyzed and elaborated to formulate a more accessible conceptual understanding of the doctrine of the Holy Trinity through Hindu–Christian meditative dialogue. The findings indicate that Hindu–Christian meditative dialogue can serve as an effective medium for explaining and understanding the doctrine of the Holy Trinity in a clearer, deeper, and more contextual manner.